Effect of Mass Composition on Nano Zircon Synthesize from Local Zircon Sand Using Soda-Precipitation-Calcination-Caustic Fusion Method - Sari, Alvika Meta; Ramadhan, Anwar Ilmar; Rahardja, Istianto Budhi; Umar, Efrizon; Yudistirani, Sri Anastasia; Faisal, Akmal Imam; Fikriyansyah, Fikriyansyah; Azmi, Wan Hamzah (Jurnal Teknologi, 2024)
Zircon sand has the major component of ZrO2 with impurities SiO2, Fe2O2, and TiO2. Zircon sand can be synthesized using various methods, such as caustic fusion method. This research purposed to determine the effect of the mass composition of NaOH on fusion process of zircon sand and to find the optimal mass ration of NaOH on yield and characteristics of nano zircon produced. This research was conducted using caustic fusion and precipitation process to obtain the mass ration of NaOH in best zircon sand fusion (melting) process. The nano zircon obtained was analyzed its size using SEM and chemical composition using FTIR. The result show that the correlation between NaOH ration and yield following the equation y = 0.42x2-2.532x+3.908 and R2 =0.9696. It showed that the higher NaOH composition will reduce the size of nano zircon. The optimum NaOH ratio is 1 : 3.6 with size od 41.983 nm and yield 1.84% which in white, odorless and powder texture. The FTIR spectrum showed the presence of the -Zr-O2 functional groups at wave numbers 600 – 700 cm-1.